Tuberculoma Induced Seizures - R. James Salway; Shruti Sangani; Samira Parekh; Sanjay Bhatt (Western Journal of Emergency Medicine, 2015)
Seizures in human immunodeficiency virus (HIV) patients can be caused by a wide variety of opportunistic infections, and, especially in developing countries, tuberculosis (TB) should be high on the differential. In India, TB is the most common opportunistic infection in HIV and it can have several different central nervous system manifestations, including intracranial tuberculomas. In this case, an HIV patient presenting with new-onset seizure and fever was diagnosed with tuberculous meningitis and multiple intracranial tuberculomas. The patient received standard TB medications, steroids, and anticonvulsants in the emergency department and was admitted for further care.